Renewable Sugars From Oil Palm Frond Juice as an Alternative Novel Fermentation Feedstock for Value-Added Products - Mior Ahmad Khushairi, Mohd Zahari; Jailani, Salihon (Elsevier, 2012)
In this paper, we report that pressed juice from oil palm frond (OPF) contained renewable sugars such as glucose, sucrose and fructose. By using a simple sugarcane press, 50% (wt/wt) of OPF juice was obtained from fresh OPF. The glucose content in the juice was 53.95 ± 2.86 g/l, which accounts for 70% of the total free sugars. We have examined the effect of various OPF juice concentrations on the production of poly(3-hydroxybutyrate), P(3HB) by Cupriavidus necator CCUG 52238T. The cell dry mass in shake flask experiment reached 8.42 g/l, with 32 wt.% of P(3HB) at 30% (v/v) of OPF juice, comparable with using technical grade sugars. The biopolymer had a molecular mass, Mw of 812 kDa, with a low polydispersity index of 1.61. This result indicates that OPF juice can be used as an alternative renewable carbon source for P(3HB) production and has potential as a renewable carbon source.